تحلیل سوسیولوجي لمنطق الممارسات الیومیة داخل المدرسة الجزائریة - طويل, فتيحة (University of Eloued جامعة الوادي, 2020)
This study aims at presenting a sociological analysis of the various daily practices within the school, which are based on a wide range of methods and forms of the logic of the educational act, such as the logic of values, personal interests and social roles ... as suggested by the sociological experience of the school system, , And their interpretation and the conversion of their subjective meaning to realistic facts, which impose itself on the human consciousness, which is detailed in the details of daily living within the Algerian school, and the issues of thorny issues before the differences on the level of scholastic success, and the quality of the relationship Social in the classroom, and the manifestations of social inequality, and the reluctance of pupils and the quality of the actors who function of socialization, and the issue of social integration ... and other issues that live by the Algerian school diary.
الملتقى الوطني الأول حول المدرسة الجزائرية الإشكالات والتحديات 18- 19 فيفري 2020. جامعة الوادي
Keywords: منطق الفعل التعلیمي المدرسي، سوسیولوجیة التجربة المدرسیة، المدرسة الجزائریة; The logic of the school educational act, the sociology of the school experiment, the Algerian school.